Seasonal sector trades : 2014 Q1 strategies - Hirsch, Jeffrey A. (Wiley, 2014)
Strategies identifying the best-performing seasonal trades for the first quarter of 2014 Seasonal tendencies and cycles provide a foundation for profitable trading. This edition of Seasonal Sector Trades contains trade ideas and strategies for the first quarter (Q1) of 2014. It identifies the best trades for each month based on historic tendencies and cycles. A special report is issued covering stocks, bonds, currencies, energy, metals, grains, soft commodities, and meats. Concise and to-the-point, the report describes monthly price tendencies for each market, alerting you to major trading opp.